Exposure to mercury and toxic trace elements in waste gold extraction in Sri Lanka: A study on an under-recognised occupational health hazard - Diyabalanage, Saranga; Manthrirathna, M.A.N.C.; Lakmali, Madhusha; Jayasinghe, R.M.N.P.K.; Werahera, Mahinda; Chandrajith, Rohana (Environmental research, 2025)
The "Minamata Convention on Mercury" aims to reduce and monitor environmental mercury (Hg) pollution, particularly from anthropogenic sources. The small-scale jewellery sector (SSJS) is recognised as a significant contributor to environmental Hg emissions and a critical route of exposure to humans. This study provides the first assessment of Hg and selected trace element exposure among individuals working in the SSJS. After microwave-assisted acid digestion, urinary concentrations of total Hg and selected trace elements were measured in 50 exposed subjects and 34 controls by inductively coupled plasma mass spectrometry. In the exposed group, creatinine-adjusted urinary Hg concentrations ranged from 0.09 to 414 μg/g creatinine, compared to 0.09–18.3 μg/g creatinine in the control group. Notably, 8 % of exposed subjects had Hg concentrations in the alarming range (5–20 μg/g creatinine), and 6 % exceeded the WHO occupational exposure limit by 4- to 8-fold. The highest risk of exposure was found in communities classified as waste gold processors. Increased urinary concentrations of cobalt (Co), arsenic (As), silver (Ag), cadmium (Cd), tin (Sn), vanadium (V), and chromium (Cr) in exposed individuals indicate possible co-exposure to multiple toxic elements. In addition, 30 % of the exposed individuals reported neurological symptoms, including numbness and fatigue, which may be related to Hg toxicity. These findings suggest significant Hg exposure among SSJS workers and highlight the critical need for targeted risk communication, regulatory interventions, and enhanced biomonitoring with additional biomarkers to assess the health impacts of metal exposure in this sector. [Display omitted] •Urinary biomonitoring revealed elevated Hg levels in exposed SSJS workers.•Waste gold separators had the highest urinary Hg concentrations.•Six percent of workers showed urinary Hg levels up to 8 times above the WHO thresholds.•Significant co-exposure to multiple toxic elements was identified.•Neurological symptoms were reported in 30 % of exposed individuals.